Marathon [compact disc, unabridged] - Freeman, Brian, 1963- (Freeman, Brian, 1963- Jonathan Stride novel., 2017)
When a bombing at the Duluth Marathon kills and injures numerous victims, detective Jonathan Stride teams up with Serena Dial, Maggie Bei and their FBI contacts to track down a suspicious man with a backpack in the wake of media misinformation.